2002
DOI: 10.1111/j.1151-2916.2002.tb00312.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Evolution and Weak Interface Development within Chemical‐Vapor‐Deposited Zirconia Coating Deposited on Hi‐Nicalon™ Fiber

Abstract: The phase contents and morphology of a ZrO 2 fiber coating deposited at 1050°C on Hi-Nicalon TM by chemical vapor deposition (CVD) were examined as a function of deposition time from 5-120 min. The morphological evolution in the ZrO 2 coating was correlated to the development of delamination within the ZrO 2 coating. The delamination appears to occur as a result of: (i) continuous formation of tetragonal ZrO 2 nuclei on the deposition surface; (ii) martensitic transformation of the tetragonal phase to a monocl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 17 publications
0
22
0
Order By: Relevance
“…18(and refs therein) Besides named factors, the influence of supports on the mechanism of tetragonal ZrO 2 phase nucleation (for coatings and films) must be taken into consideration too 19 . For example, the stabilization of t-ZrO 2 phase was observed not only for monolithic ceramic specimens but also within the CVD ZrO 2 coating on SiC fiber by Li et al 2,3 The authors noted also that a free carbon presenting as an impurity in coating can also influence on the stabilization of the tetragonal modification. It could be proposed with discretion that the Zr O Si bonds the formation of which at the Nicalon TM fiber/ZrO 2 coating interface was confirmed using Xray photoelectron spectroscopy by Baklanova et al 8 appear to be considered as stabilizing factor.…”
Section: Micro-raman Spectra Of the Y-psz Coated Nicalon Tm Fibersmentioning
confidence: 94%
See 1 more Smart Citation
“…18(and refs therein) Besides named factors, the influence of supports on the mechanism of tetragonal ZrO 2 phase nucleation (for coatings and films) must be taken into consideration too 19 . For example, the stabilization of t-ZrO 2 phase was observed not only for monolithic ceramic specimens but also within the CVD ZrO 2 coating on SiC fiber by Li et al 2,3 The authors noted also that a free carbon presenting as an impurity in coating can also influence on the stabilization of the tetragonal modification. It could be proposed with discretion that the Zr O Si bonds the formation of which at the Nicalon TM fiber/ZrO 2 coating interface was confirmed using Xray photoelectron spectroscopy by Baklanova et al 8 appear to be considered as stabilizing factor.…”
Section: Micro-raman Spectra Of the Y-psz Coated Nicalon Tm Fibersmentioning
confidence: 94%
“…Recently the feasibility of using a CVD ZrO 2 fiber coating as an oxidation-resistant and weak interphase for structural composite materials such as SiC/SiC (CMC's) was proposed and thoroughly studied by Lee et al [1][2][3][4] They found that the CVD ZrO 2 interfacial coating on Nicalon type fiber exhibited desired tensile failure behavior, extensive crack deflection within the interface region and fiber debonding (i.e. weak interface behav- * Corresponding author.…”
Section: Introductionmentioning
confidence: 99%
“…As was noted by Lee and coworkers, 8 not only the weak interface character but the integrity and uniformity of the fiber coating are important in terms of protecting the fiber surface from matrix infiltration by CVI or melt infiltration. From this point of view, a dense undelaminated but compressively stressed coating, e.g.…”
Section: Discussionmentioning
confidence: 89%
“…Besides, it was detected the relationships between the oxygen partial pressure and the nucleation and morphologic characteristics of the ZrO 2 coating that was formed by CVD or magnetron sputtering methods. [7][8][9]11 These relationships were attributed to the grain size and oxygen deficiency effects, which appear to cause the stabilization of t-ZrO 2 . Thus, one can see that the ZrO 2 coating composed of predominantly tetragonal or cubic transformable phases can be fabricated with different experimental approaches.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation